An approach to diagnostic dilemma in thyroid cytopathology - Pant, R (Journal of Pathology of Nepal, 2012)
Journal of Pathology of Nepal (2012) Vol. 2, 338-339 DOI: http://dx.doi.org/10.3126/jpn.v2i4.6892